Complete Bash Shell Scripting - Polu, Narendra (Packt Publishing, 2020)
Automate repetitive tasks with Bash Shell Scripting to save valuable time About This Video Learn the basics of Bash Shell Scripting Explore the input and output commands for shell scripting Understand arithmetic operators with detailed explanations In Detail This course is designed to help you automate repetitive tasks and master Bash Shell Scripting easily. With most organizations adopting the open source Linux and Unix operating systems, there is an ever-increasing demand for developers with Linux and Unix skills. This course covers command-line commands and Bash Shell Scripting extensively to help you become a Linux\Unix OS expert.